Technological Universities of India to Achieve Global Quality and Excellence - Ratnalikar, N. V.; Patil, Sunil (Journal of Engineering Education Transformations, 2018)
There is a large number of Technological and Technical Universities in India but unfortunately none of their rank in global ranking with the exception of few premier institutes/universities. These universities are functioning under a highly regulated environment which restricts the level of freedom required for responding to the fast changes happening in the industry. The end result is the graduates passing out of these universities are not employable. This scenario must be changed hence authors of this paper have investigated what ails the technical education system in India. Apart from excessive regulations, large number of colleges affiliated to a university, education treated as a business instead of places for academic excellence and research, and lack of innovations on the part of faculty and students, adoption of quality standards in research, teaching, and management is an absolute imperative to improve existing system. Authors have proposed various programs to be designed and implemented to improve quality in engineering education. The regulatory agencies have also proposed few programs but implementation at the university and colleges/institute level remains questionable. These programs must be championed by the top management of these organizations and adequate funding must be allocated else the importance of these programs gets limited to showing documents and saying right things in front of accrediting agencies at the time of assessment.